2020
DOI: 10.1038/s41467-020-17468-y
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting QKI-7 in vivo restores endothelial cell function in diabetes

Abstract: Vascular endothelial cell (EC) dysfunction plays a key role in diabetic complications. This study discovers significant upregulation of Quaking-7 (QKI-7) in iPS cell-derived ECs when exposed to hyperglycemia, and in human iPS-ECs from diabetic patients. QKI-7 is also highly expressed in human coronary arterial ECs from diabetic donors, and on blood vessels from diabetic critical limb ischemia patients undergoing a lower-limb amputation. QKI-7 expression is tightly controlled by RNA splicing factors CUG-BP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…In addition, as we have also reported [ 21 ], QKI5 played a crucial role in differentiating ECs from induced pluripotent stem cells (iPSCs) via stabilization of VE-cadherin and Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) activation through Signal Transducer and Activator of Transcription 3 (STAT3) signaling. Furthermore, we showed QKI-7 to bind and promote mRNA target degradation such as of VE-cadherin, while the knockdown of QKI7 in a diabetic mouse model of hindlimb ischemia significantly restored reperfusion and blood flow in vivo [ 22 ].…”
Section: Rbps In the Pathogenesis Of Diabetes And Cardiovascular Diseasementioning
confidence: 99%
“…In addition, as we have also reported [ 21 ], QKI5 played a crucial role in differentiating ECs from induced pluripotent stem cells (iPSCs) via stabilization of VE-cadherin and Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) activation through Signal Transducer and Activator of Transcription 3 (STAT3) signaling. Furthermore, we showed QKI-7 to bind and promote mRNA target degradation such as of VE-cadherin, while the knockdown of QKI7 in a diabetic mouse model of hindlimb ischemia significantly restored reperfusion and blood flow in vivo [ 22 ].…”
Section: Rbps In the Pathogenesis Of Diabetes And Cardiovascular Diseasementioning
confidence: 99%
“…In a different study, RNA-binding protein Quaking-7 (QKI-7) was found to be upregulated in iPSC-ECs after exposure to hyperglycemia and in hiPSC-ECs from diabetic patients. QKI-7 upregulation was correlated with disrupted cell barrier, enhanced monocyte adhesion, and compromised angiogenesis, suggesting this protein as a possible new strategy for the treatment of diabetic vascular complications [105]. Another approach could be the use of information from genome-wide association studies (GWAS), which have successfully identified a large number of genetic loci associated with risks of complex traits in cardiovascular diseases.…”
Section: Complex Vascular Disease-diabetesmentioning
confidence: 99%
“…Under hypoxia, QKI directly regulated hypoxia‐induced factor‐1a (HIF‐1α) expression to support tumorigenesis 14 . QKI isoforms have also been implicated in altering vascular endothelial growth factor receptor (VEGF‐R)/ Neuropilin‐1 (NRP1) co‐receptor signalling pathway in endothelial cell differentiation and functions 15,16 . They can compete with microRNAs to inhibit gene expression of NRP‐1/2 that are essential for early cell development 13 .…”
Section: Introductionmentioning
confidence: 99%